2013
DOI: 10.1007/s10935-013-0312-5
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Preferences for the Prevention of Intimate Partner Violence Among Hispanics: A Community’s Perspective

Abstract: Research suggest that Hispanics in the U.S. are disproportionately affected by the consequences of intimate partner violence. Nevertheless, few intimate partner violence prevention interventions have been developed to address the unique needs and preferences of this population. The Partnership for Domestic Violence Prevention is a community-based participatory research project that assessed the needs and preferences for prevention programs for Hispanics in Miami-Dade County. Nine focus groups with domestic vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 38 publications
4
81
0
1
Order By: Relevance
“…85 For IPV prevention programs targeting Hispanic and Black women, it is not only important to learn about the needs and preferences of these groups in general, but to tailor prevention and treatment strategies for different subgroups, accounting for possible confounding factors unique to these groups including immigration, acculturation levels, traditional gender roles, historical racism, and other socioeconomic and environmental factors that may influence health outcomes. 31,86 …”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…85 For IPV prevention programs targeting Hispanic and Black women, it is not only important to learn about the needs and preferences of these groups in general, but to tailor prevention and treatment strategies for different subgroups, accounting for possible confounding factors unique to these groups including immigration, acculturation levels, traditional gender roles, historical racism, and other socioeconomic and environmental factors that may influence health outcomes. 31,86 …”
Section: Implications For Prevention and Treatmentmentioning
confidence: 99%
“…The center provided coordinated, comprehensive, and compassionate services to victims of IPV, sexual violence, and human trafficking; their children; and the general community. The need for HIV services at the center was identified through prior community-based participatory research conducted by Gonzalez-Guarda, Cummings, Becerra, Fernandez, and Mesa (2013). The study reported here sought to complement and extend the work being done by the parent study by examining the barriers, facilitators, and decision-making processes involved as part of the HIV testing program from the perspectives of both providers and clients.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, scholars worked within existing community structures to convene groups of individuals to respond to the expressed needs of the community, which had been identified in previous research and disseminated through publications coauthored with community partners. 31, 32, 3739 Although these CABs were formed after the research projects were initiated, they played an influential role in developing interventions to address priority problems in the communities. Communities engaged in the CABs had different preferences in the role they wanted to take in the organization of the boards.…”
Section: Discussionmentioning
confidence: 99%
“…For example, community members led focus group discussions with community members, delivered a teen dating violence prevention program for Hispanic families, and worked with academics to analyze and publish results. 36, 37 …”
Section: Working With Cabs In Diverse Communitiesmentioning
confidence: 99%